Length–weight and length–length relationships of five fish species from the Dadu River and its tributaries, southwest China. (14th July 2017) - Zhang, Zhiming; Wang, Wenjun; Chen, Feng; Yang, Zhengqing
Summary: Length‐weight (LWRs) and length–length (LLRs) relationships are reported for five fish species belonging to two families and five genera from the Dadu River and its tributaries, southwest China. In total, 605 specimens were collected by electrofishing and gillnets (mesh size ranging from 1.5 to 3.5 cm) in May and October 2013, May and October 2014, May and November 2015, and April and October 2016. The b ‐values for LWRs varied from 2.571 to 2.952 ( r 2  > .915). The results further indicated that the LLRs were highly correlated ( r 2  > .978; p  < .01). The two LWRs, five LLRs, and two maximum lengths are presented to FishBase for the first time. This biometric data and their relationships are relevant to the management and conservation of local fishes and fisheries.